Analyzing the Content of the Arabic Language Series Book for Teaching Arabic to Non-Native Speakers: A Study in the Context of William Francis Mackey: تحليل محتوى كتاب سلسلة اللغة العربية لتعليم اللغة العربية لغير الناطقين بها: دراسة في سياق وليام فرانسيس ماكي - Asbarin, Asbarin; Wargadinata, Wildana; Rusuly, Usfiyatur; Nailil Amalia, Nabila (Journal of Arabic Language Learning and Teaching (JALLT), 2024)
The aim of this research was to evaluate the compatibility of the content within the book "Silsilatul Lisānil'Arabi lita'līmi Lughatil 'Arabiyati Ligairin Nātiqīna Bihā" with William Francis Mackey's four standards for developing teaching materials, namely: selection, gradation, presentation, and repetition of material. This descriptive literature study utilized observational techniques, interviews, and reading methods for data collection. The data analysis employed the Krippendorff content analysis model, involving data collection, sampling, recording, analysis, and conclusion stages. Findings indicate that the content of the Silsilatul Lisānil'Arabi book for beginners level 1 aligns with Mackey's principles, encompassing the selection of material based on objectives, student proficiency, study duration, language choice, and learning feasibility factors. Additionally, the material demonstrates appropriate gradation through grouping and sequencing, effective presentation methods including differentiation processes, potential producers, pictorial procedures, and contextual procedures, as well as suitable repetition strategies covering listening, speaking, reading, and writing skills.